AMBER Alert: An Ironic Antidote to “Missing White Girl Syndrome”? - Griffin, Timothy (Criminal justice review, 2025)
“Missing White Girl Syndrome” (MWGS) has been coined in critique of news media coverage favoritism of victims fitting that description. The AMBER Alert child recovery system was in fact inspired by the abduction and murder of a missing white girl, and some have argued its issuance decisions reflect MWGS. We examine this question using secondary data, including the annual AMBER Alert reports provided by the National Center for Missing and Exploited Children (NCMEC), the National Incidence Studies of Missing, Abducted, Runaway, and Thrownaway Children (NISMART), and the National Crime Information Center (NCIS). We compared the demographics of victims from official AMBER Alert data (NCMEC) with cross-comparable demographics from the two official missing persons data sources to test for potential main-effect bias favoring whites or girls. A fourth dataset derived from media accounts of AMBER Alerts is used to test for any potential interaction effect of issuance preference for white girls. Overwhelmingly the findings suggest AMBER Alert issuance decisions do not reflect MWGS. Thus, we argue the system has the potential to function as an ironic “antidote” to MWGS by virtue of the identities of the children for whom it is routinely deployed. However, we qualify by acknowledging limitations with available data, and that the “black box” of AMBER Alert issuance decisions remains unstudied, leaving open the question of race and/or gender bias occurring at that point. Policy discourse and future research implications are discussed.